Towards a New Curriculum for Humanitarian Studies? Report on Workshop - Feinstein International Center (Tufts Archival Research Center, 2005)
In April 2002 the Feinstein International Famine Center applied for a renewal of a grant from the Andrew Mellon Foundation to support its work in teaching and research on humanitarian issues. One of the proposed outcomes from the grant was to initiate a discussion with other universities that are teaching similar courses to explore areas of convergence, research and teaching methodologies and other aspects relating to the development of what is now a growing field or sub- field called âHumanitarian Studiesâ.